Combined axial and lateral rotary cutting mechanism for chopping oil palm frond - Alnuaimi, Wadhah Noori Humadi (2017)
The oil palm frond (OPF) is one of the most abundant agricultural by-products in Malaysia and has great potential to be utilized as mulch, fuel, animal feed constituent and fertilizer constituent. Today, it is also an important resource in various modern industries such as pulp and paper, fiberboard and biodegradable film. However, these benefits could not be realized fully due to the absence of a suitable way of reducing the size of the fronds conveniently and economically. Moreover, the high cost of size reduction machines due to high-power requirement, large size and lack of mobility inside the field cause the farmer to bear the transportation costs of moving oil palm fronds outside the field to chop. This necessitated the need to design a new cutting mechanism which commensurate with the physical and mechanical properties of oil palm fronds in order to get the best performance with less energy consumption. Hence, this will reduce the cost of the machine and increase farmer’s income through the sale of the chopped materials.